Evaluation Of Tannin As Natural Coagulant For Pulp And Paper Mill Wastewater Treatment - Fadzil, Nurul Farahanes Mohd
Basically, pulp and paper mills generated million tons of highly polluted wastewater every year. The quality of the wastewater is totally depends on the different types of pulping processes. In this research work, pulp & paper mills wastewater from Nibong Tebal Paper Mill have been collected and treated by using natural coagulant (Tannin) and alum. The effects of dosing rate and pH are examined for reduction of COD, SS, turbidity and colour by using jar testing. High COD and suspended solid concentration was recorded at 620 to 740 mg/L and 2015 to 3550 mg/L respectively. Based on the jar testing results, the optimum dose and optimum pH for tannin was recorded at 200 mg/L and pH 3 while the optimum dose and optimum pH for alum are 300 mg/L and pH 9. The removal of COD, SS, turbidity and colour were 77.42 to 95.95 %, 87.32 to 96.50 %, 99.98 to 100 % and 87.00 to 88.10 % by using alum. The percentage removals of COD, SS, turbidity and colour for tannin were 47.26 to 74.32 %, 90.78 to 97.18 %, 99.29 % and 16.67 to 34 %. The results had shown that tannin can removed suspended solid which was at range 90.78 to 97.18 % but not to other parameters. However, the study proved that tannin is not suitable for the purpose of removing colour as the percentage removal of this experiment range between 16.67 to 34 % only. Thus, future study is essential in determining effectiveness colour removal percentage.